Clinical Outcomes of Unrelated Umbilical Cord Blood Graft vs. Haploidentical Donor Transplantation: Critical Issues for an Adequate Comparison - Vanegas, Diana; Niño-Quiroga, Laura; Chaparro, Mauricio; Camacho-Rodríguez, Bernardo; Estupiñán, Marcela; Perdomo-Arciniegas, Ana-María (Frontiers in Medicine, 2021)
Unrelated umbilical cord blood (UCB) and haploidentical grafts have been used for allogeneic hematopoietic stem and progenitor cell (HSPC) transplantation in patients without a related or non-related HLA-matched donor. The less stringent human leukocyte antigen (HLA) matching requirement in both sources raise an important possibility for patients in need of urgent transplantation to treat any hematological disease. Selection of the best alternative donor is a difficult task that will depend on donor criteria, center experience, patient disease conditions and risk, among others. Most comparisons available in scientific publications between both graft sources are obtained from retrospective analysis in wide time windows and heterogeneous number of patients, types of disease, disease stages, previous treatments, graft source, conditioning regimen, and evaluable endpoints. There is also an evident impact of the economic traits since low-income countries require less expensive treatments to satisfy the needs of the patients in the most effective possible path. Therefore, haploidentical transplantation could be an appealing option, even though it has not been completely stablished if any chronic treatment derived from the procedure could become a higher expense. Although some reports exhibit a possible trend towards graft failure in UCB and increased graft versus host disease (GVHD) in haploidentical transplantation, there are no conclusive results for overall survival, progression-free survival, transplant-related mortality, and relapse risk. This minireview focuses on comparing main issues associated with the use of both HSCP sources and provide tools for physicians which face the difficult decisions between these alternative donor sources.